2007
DOI: 10.1086/523111
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hepatitis B Virus Genotype B into 2 Major Types Based on Characterization of a Novel Subgenotype in Arctic Indigenous Populations

Abstract: Hepatitis B virus genotype B (HBV/B) has been classified into 5 subgenotypes. Except for Bj/B1 in Japan, the subgenotypes (Ba/B2-B5) have undergone recombination with HBV/C in the core promoter/precore/core genomic region. Phylogenetic analyses of complete sequences show that the Arctic strains belong to a novel subgenotype (HBV/B6) without the recombination, analogous to what is seen with Bj/B1. Comparison of 50 HBV/B6 carriers from the Arctic versus 50 Bj and 50 Ba age- and sex-matched carriers from Asia rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 15 publications
5
81
0
Order By: Relevance
“…5 One previous case-control study found that persons infected with genotype B had a significantly higher rate of HBsAg clearance than those infected with genotype C. 19 However, based on the geographic distribution of HBV genotypes, genotype B in this study was likely to be B Asia (B2-5), whereas the genotype B found in Alaska Native carriers is a new subtype (B6) that is more closely related to B Japan (B1). 21 Persons who cleared HBsAg have been tested for HBV DNA in three studies. Presence of HBV DNA varied widely and was found in 1.3% and 1.7% at 12 months, 17,22 1.1% at 49 months, 23 and 21.4% at 5 years and 14.3% at 10 years after clearance.…”
Section: Discussionmentioning
confidence: 99%
“…5 One previous case-control study found that persons infected with genotype B had a significantly higher rate of HBsAg clearance than those infected with genotype C. 19 However, based on the geographic distribution of HBV genotypes, genotype B in this study was likely to be B Asia (B2-5), whereas the genotype B found in Alaska Native carriers is a new subtype (B6) that is more closely related to B Japan (B1). 21 Persons who cleared HBsAg have been tested for HBV DNA in three studies. Presence of HBV DNA varied widely and was found in 1.3% and 1.7% at 12 months, 17,22 1.1% at 49 months, 23 and 21.4% at 5 years and 14.3% at 10 years after clearance.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with a high endemic rate of HBV infection, incidence of HCC and cirrhosis were not substantially different from Denmark [73][74], which is not considered endemic due to an HBsAg prevalence of 0.1% [75]. Genotype D and B5 are predominant in Greenland, and a high incidence of B5 infection may explain the relatively low occurrence of HCC and cirrhosis [76][77].…”
Section: Hbv Epidemiologymentioning
confidence: 83%
“…HBV/B1, the most phylogenetically similar subgenotype to HBV/B5, had 8% of patients progress to end-stage liver disease, while HBV/B2, a 'recombinant' genotype B, had 28% of patients progress to end-stage liver disease [76].…”
Section: Hbv Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations